First-order phase transitions in Yang-Mills theories and the density of state method - Biagio Lucini (Physical Review D)
When studied at finite temperature, Yang-Mills theories in 3 + 1 dimensions display the presence of confinement/deconfinement phase transitions, which are known to be of first order—the SU(2) gauge theory being the exception. Theoretical as well as phenomenological considerations indicate that it is essential to establish a precise characterisation of these physical systems in proximity of such phase transitions. We present and test a new method to study the critical region of parameter space in non-Abelian quantum field theories on the lattice, based upon the Logarithmic Linear Relaxation (LLR) algorithm. We apply this method to the SU(3) Yang Mills lattice gauge theory, and perform extensive calculations with one fixed choice of lattice size. We identify the critical temperature, and measure interesting physical quantities near the transition. Among them, we determine the free energy of the model in the critical region, exposing for the first time its multi-valued nature with a numerical calculation from first principles, providing this novel evidence in support of a first order phase transition. This study sets the stage for future high precision measurements, by demonstrating the potential of the method.